Bertrand Russell, The Utilitarian Pacifist - Olivier Esteves (Revue Française de Civilisation Britannique)
Bertrand Russell (1872-1970), one of the towering intellectuals of the 20th century, was an indefatigable pacifist throughout the Great War. But his pacifism was not unreserved, depending as it did on his consequentialist attitude towards war and towards pacifism. This chapter gives a description and analysis of the key stages in Russell’s political itinerary from 1914 to 1918 : on the declaration of war, on the introduction of conscription, at the time of the Russian revolutions and when there appeared the prospect of profound social and political changes in Britain.